Cyclic RGD‐Coated Ultrasmall Gd2O3 Nanoparticles as Tumor‐Targeting Positive Magnetic Resonance Imaging Contrast Agents. Issue 26 (28th June 2018) - Ahmad, Mohammad Yaseen; Ahmad, Mohammad Wasi; Cha, Hyunsil; Oh, In‐Taek; Tegafaw, Tirusew; Miao, Xu; Ho, Son Long; Marasini, Shanti; Ghazanfari, Adibehalsadat; Yue, Huan; Ryeom, Hun‐Kyu; Lee, Jongmin; et al.
Abstract : The excellent theranostic properties of gadolinium oxide (Gd2 O3 ) nanoparticles (GNPs) make them very useful as high‐performance positive magnetic resonance imaging ( T 1 MRI) contrast agents, X‐ray computed tomography (CT) contrast agents, and gadolinium neutron capture therapy (GdNCT) agents in tumor targeting. Among these applications, tumor‐targeting T 1 MRI is investigated in this study. To this end, we employ cyclic RGDs (cRGDs; cyclic Arg–Gly–Asp peptides) as tumor‐targeting ligands to coat ultrasmall GNPs (particle diameter = 1.0–2.5 nm). Five types of commercial cRGDs are used in the coating. The cRGD‐coated GNPs (cRGD‐GNPs) are prepared through one‐pot syntheses. They exhibit longitudinal water‐proton relaxivity ( r 1 ) values of 10.0–18.7 s –1 mm –1, with r 2 / r 1 ratios of 1.4–1.7 ( r 2 = transverse water‐proton relaxivity), which are 3–5 times higher than those of commercial Gd chelates. The in vivo tumor targeting of the cRGD‐GNPs is demonstrated by taking T 1 MR images in a model mouse with a liver tumor using one of the five cRGD‐GNP sample solutions prepared. Approximately threefold contrast enhancements are observed in the T 1 MR images in the tumor region of the liver than in the normal part of the liver, following intravenous administration of the solution. These results demonstrate that cRGD‐GNPs are potential tumor‐targeting T 1 MRI contrast agents. Abstract : cRGD‐coated ultrasmall GNPs with diameters of 1.0–2.5 nm are prepared in a one‐pot synthesis and applied to tumor‐targeting MRI in vivo. Greater contrast enhancements in the T 1 MR images are observed in the tumor than in normal tissue, demonstrating that cRGD‐GNPs could be a potential tumor‐targeting T 1 MRI contrast agent.